PERAN HAKIM MENERAPKAN KEADILAN: STUDI KASUS PENGGUGAT KLAIM BEBERAPA ASET PADA PENYELESAIAN SENGKETA HARTA BERSAMA - Muddin, Ilhammuddin; Elfia; Zulfan (Fakultas Hukum Universitas Islam Syekh Yusuf, 2024)
This study reviews court decisions in resolving joint property disputes, focusing on analyzing the decision in case number 0000/Pdt.G/2022/PA.Kds. The division of inherited property is a complicated problem because it often causes conflict among heirs. This research is library reasearch by examining phenomena that occur in society, using secondary data sources in the form of relevant literature studies, followed by qualitative descriptive analysis. The results showed that the decision in the settlement of joint property disputes was based on Article 35 paragraph (1) of Law Number 1 of 1974 and the Compilation of Islamic Law, which emphasized that property obtained during marriage becomes joint property. The plaintiff's claim to several assets as joint property was partially recognized by the defendant after careful examination. Keywords: Asset, Judge, Justice, Dispute Resolution